Guide pour l'évaluation de l'agroécologie (éditions Quae, 2023)
The Guide for the evaluation of agroecology proposes an approach and methodological tools to assess, on the one hand, the effects of agroecological practices and systems on the agro-environmental and socio-economic performance of agriculture and, on the other hand, the conditions for the development of agroecology. It aims to help development actors to better design their projects, programmes and public policies in favour of agroecology, to facilitate the creation of references (performance and development conditions) and to support farmers so that they can better evaluate the results of their practices and thus have a decision-making aid. This guide is divided into three parts. The first part presents the general approaches to spot evaluation and monitoring-evaluation. The second part consists of evaluation sheets dealing either with the elements on which agroecology is likely to have effects in the agro-environmental and socio-economic fields, or with the conditions for its development. Finally, the third part offers methodological complements in the form of tool sheets. This book is the result of collaboration between teams from GTAE (Agrisud International, AVSF, Cari and GRET), AgroParisTech, CIRAD, IRD and the Institut Agro Montpellier.